2008
DOI: 10.4028/www.scientific.net/amr.47-50.718
|View full text |Cite
|
Sign up to set email alerts
|

Complex Multifunctional Materials for Special Applications

Abstract: Elaboration of complex multifunctional materials with nanometric structure and controlled characteristics for special applications, implies the use of advanced techniques of powder metallurgy such as mechanical alloying, allowing the structural modeling and designing of material properties. The aims of paper consist in the development of complex multifunction materials with nanometric structure for special use (civil and/or military) for industrial applications. The paper presents briefly some aspect regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In their works, the problem of ensuring the fullest life of a cutting tool from various positions was studied: Vasin S.A. [2], Grigoriev S.N. [3], Carceanu, I., Cosmeleatǎ, G. [4], Ferri, C. [5], Kümmel, J. [6], Munish Kumar Gupta [7], Murthy, K.S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their works, the problem of ensuring the fullest life of a cutting tool from various positions was studied: Vasin S.A. [2], Grigoriev S.N. [3], Carceanu, I., Cosmeleatǎ, G. [4], Ferri, C. [5], Kümmel, J. [6], Munish Kumar Gupta [7], Murthy, K.S.…”
Section: Introductionmentioning
confidence: 99%
“…A literature analysis of world-renowned works in the field of mechanical blade cutting of metals showed that the temperature factor has a resulting effect on the cutting process of difficult-toprocess materials [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%